1994
DOI: 10.1121/1.408859
|View full text |Cite
|
Sign up to set email alerts
|

The application of frequency and time domain kurtosis to the assessment of hazardous noise exposures

Abstract: Five computer synthesized broadband noises, each having the same average spectrum and the same unweighted Leq of 100 dB SPL but very different temporal structures were used to produce hearing loss in chinchillas. Despite the same exposure energies and spectra, each noise exposure produced a different magnitude and frequency distribution of hearing loss and sensory cell loss. The results indicate that the statistical properties of a signal are important in the determination of hearing loss. When the audiometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Impulse peak levels generally exceed 140 dB whereas impact peak levels are usually lower than 140 dB, 7 but the durations of impacts are often longer because of differences in the sound sources themselves and also due to the reverberation and reflection characteristics of indoor environments. Both impulses and impacts may be superimposed on a background of continuous or varying noise, which increases the hazard to hearing, [8][9][10][11] as will be discussed in subsequent paragraphs.…”
Section: Attempts To Define Non-gaussian Noisementioning
confidence: 99%
See 3 more Smart Citations
“…Impulse peak levels generally exceed 140 dB whereas impact peak levels are usually lower than 140 dB, 7 but the durations of impacts are often longer because of differences in the sound sources themselves and also due to the reverberation and reflection characteristics of indoor environments. Both impulses and impacts may be superimposed on a background of continuous or varying noise, which increases the hazard to hearing, [8][9][10][11] as will be discussed in subsequent paragraphs.…”
Section: Attempts To Define Non-gaussian Noisementioning
confidence: 99%
“…Complex Noise-Animal Experiments For many years, investigators have found that noise exposures that include impulse or impact noise produce greater than expected damage to the auditory system, in both animals and humans. 8,10,[94][95][96] This observation led some to recommend a penalty to the permissible limits for complex noise exposures with a substantial component of impulse/impact noise. Evidence of this appears in Note #3 of ISO 1999 and Note #2 of an earlier version, 13,20 where caution is advised for impulsive or tonal conditions, which could be considered 5 dB more harmful than broadband, steady, nontonal noise.…”
Section: Measurement Of Complex Noisementioning
confidence: 99%
See 2 more Smart Citations
“…Damage percentage of outer and inner hair cell loss based on different beta values, i.e., β = 3 (A), β = 21 (B), β = 84 (C), and its potential pure-tone audiometric results. It is a graphical display inferred from data ofLei et al (1994). OHC: outer hair cell, IHC: inner hair cell.…”
mentioning
confidence: 99%